“It’ll Grow Organically and Naturally": The Reciprocal Relationship between Student Groups and Disability Studies on College Campuses - Stout, Allegra; Schwartz, Ariel (Disability Studies Quarterly, 2014)
Although few colleges and universities offer undergraduate disability studies curricula, our own experiences suggest that higher education settings provide opportunities for students to engage with and act upon disability studies theories and concepts. To learn more about the interactions between undergraduate student groups and disability studies, we interviewed students and faculty on three campuses. We found that students not only access disability studies theory through both formal and informal means, but that they also actively engage with it to develop their understandings of disability and interpret their experiences. Additionally, student groups educate their campus communities by advocating for the inclusion of disability studies in curricula, sharing their perspectives in the classroom, and hosting events related to disability studies. Through these activities, often in collaboration with faculty and staff, students forge reciprocal relationships between their activism and the field of disability studies. Keywords: Student groups, activism, advocacy, narrative, undergraduate education